Coordinated AR and microRNA regulation in prostate cancer - Eringyte,I; Zamarbide,Losada JN; Powell,SM; Bevan,CL; Fletcher,CE (Asian Journal of Urology, 2020)
The androgen receptor (AR) remains a key driver of prostate cancer (PCa) progression, even in the advanced castrate-resistant stage, where testicular androgens are absent. It is therefore of critical importance to understand the molecular mechanisms governing its activity and regulation during prostate tumourigenesis. MicroRNAs (miRs) are small ∼22 nt non-coding RNAs that regulate target gene, often through association with 3' untranslated regions (3'UTRs) of transcripts. They display dysregulation during cancer progression, can function as oncogenes or tumour suppressors, and are increasingly recognised as targets or regulators of hormonal action. Thus, understanding factors which modulate miRs synthesis is essential. There is increasing evidence for complex and dynamic bi-directional cross-talk between the multi-step miR biogenesis cascade and the AR signalling axis in PCa. This review summarises the wealth of mechanisms by which miRs are regulated by AR, and conversely, how miRs impact AR's transcriptional activity, including that of AR splice variants. In addition, we assess the implications of the convergence of these pathways on the clinical employment of miRs as PCa biomarkers and therapeutic targets.